Fiber Metabolism, Procollagen and Collagen Type III Immunoreactivity in Broiler Pectoralis Major Affected by Muscle Abnormalities - Maurizio Mazzoni; Francesca Soglia; Massimiliano Petracci; Federico Sirri; Giulia Lattanzio; Paolo Clavenzani (Animals, 2020)
The present study aimed to evaluate the muscle fiber metabolism and assess the presence and distribution of both procollagen and collagen type III in pectoralis major muscles affected by white striping (WS), wooden breast (WB), and spaghetti meat (SM), as well as in those with macroscopically normal appearance (NORM). For this purpose, 20 pectoralis major muscles (five per group) were selected from the same flock of fast-growing broilers (Ross 308, males, 45-days-old, 3.0 kg live weight) and were used for histochemical (nicotinamide adenine dinucleotide tetrazolium reductase (NADH-TR) and alpha-glycerophosphate dehydrogenase (α-GPD)) and immunohistochemical (procollagen and collagen type III) analyses. When compared to NORM, we found an increased proportion (p < 0.001) of fibers positively stained to NADH-TR in myopathic muscles along with a relevant decrease (p < 0.001) in the percentage of those exhibiting a positive reaction to α-GPD. In addition, an increased proportion of fibers exhibiting a positive reaction to both stainings was observed in SM, in comparison with NORM (14.3 vs. 7.2%; p < 0.001). After reacting to NADH-TR, SM exhibited the lowest (p < 0.001) cross-sectional area (CSA) of the fibers (−12% with respect to NORM). On the other hand, after reacting to α-GPD, the CSA of WS was found to be significantly larger (+10%) in comparison with NORM (7480 vs. 6776 µm2; p < 0.05). A profound modification of the connective tissue architecture involving a different presence and distribution of procollagen and collagen type III was observed. Intriguingly, an altered metabolism and differences in the presence and distribution of procollagen and collagen type III were even observed in pectoralis major muscle classified as NORM.